Prototype Sistem Pendeteksi Kebakaran Di Ruang Server Berbasis Arduino Pada Dinas Kesehatan Kendal - Nur Rokhman; Sumaryanto Sumaryanto; Puteri Anindya Maulan; Fitro Nur Hakim (Go Infotech: Jurnal Ilmiah STMIK AUB, 2026)
Arduino-Based Fire Detection System Prototype in the Server Room at the Kendal Health Service. Fire disaster is a disaster that can occur anywhere and at any time. Fires can also be caused by human negligence, natural conditions, and so on. Fire is also a problem faced by the community due to officers' delays in handling it, resulting in a lot of losses that can occur, including loss of life or material. Residents who are at the location of a fire must receive early warning information if the fire starts to get bigger. Therefore, the aim of this research is to design a fire detection tool using an Arduino Uno equipped with an extinguisher with an SMS gateway notification. This system will work where if the flame sensor and MQ-2 sensor have received fire or smoke input, the GMS module will automatically provide notification in the form of SMS to the cellphone. This fire detection system can also reduce the impact of fires which will grow and be extinguished by the water pump. installed on the tool. This fire detection tool solution can solve the problems faced by sending SMS notifications to officers and can be handled quickly by this tool.